Utilization of Tithonia diversifolia as Ruminant Feed - Juniar Sirait; Kiston Simanihuruk (Indonesian Center for Animal Research and Development, 2021)
Forage is an important component in raising ruminants. Limited land specifically for forage cultivation is a big challenge in providing forage. Tithonia diversifolia is a promising species used as feed for ruminants because it is easy to grow in various places without being cultivated, such as on roadsides or as fences. This paper aims to give information about Tithonia diversifolia and its cultivation, production, nutritional value and its utilization as forage for ruminant. This plant can be propagated vegetatively and generatively. The spread of seeds can be carried by vectors such as humans, livestock, water currents and wind. T. diversifolia plants have several advantages: fast growing, high production, high crude protein content, resistance to high cutting frequencies and tolerance to acidic soils. Apart from these advantages, this plant also has some weaknesses because it contains several secondary compounds which may affect rumen fermentation. This weakness can be overcome by addition of feed aditive, charcoal or by processing it into silage. T. diversifolia has been used as feed for small and large ruminants either as single or mixed feed with concentrates and other forages with relatively high digestibility. The dry matter consumption of T. diversifolia reaches nearly 600 g/h/d when given as single feed to goats. However, recommended feeding level is 30% of total ration.